2010
DOI: 10.1002/lary.20815
|View full text |Cite
|
Sign up to set email alerts
|

Continuous analysis and monitoring of snores and their relationship to the apnea‐hypopnea index

Abstract: A new system for automatic monitoring and analysis of snores during the night is presented. Sound intensity and several snore frequency parameters allow differentiation of snorers according to obstructive sleep apnea syndrome severity (OSAS). Automatic snore intensity and frequency monitoring and analysis could be a promising tool for screening OSAS patients, significantly improving the managing of this pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 25 publications
1
65
0
Order By: Relevance
“…Snoring sounds have been also assessed in the context of SAHS classification. A LR classifier modelled with nine spectral features reached 81.1% Acc and 0.850 AROC (AHI= 5 e/h threshold); and 86.5% Acc and 0.920 AROC (AHI = 5 e/h threshold) [54]. Another LR classifier obtained from 11 time and frequency domain features was evaluated for AHI = 10 e/h [55].…”
Section: Discussionmentioning
confidence: 99%
“…Snoring sounds have been also assessed in the context of SAHS classification. A LR classifier modelled with nine spectral features reached 81.1% Acc and 0.850 AROC (AHI= 5 e/h threshold); and 86.5% Acc and 0.920 AROC (AHI = 5 e/h threshold) [54]. Another LR classifier obtained from 11 time and frequency domain features was evaluated for AHI = 10 e/h [55].…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of 37 snorers with a range of AHI scores, demonstrated that an all-night recording with automated scoring of intensity and frequency could reliably distinguish AHI classifications (40). A large study of snoring volume intensity in 1634 snorers divided into non-OSA, mild, moderate and severe OSA found a 14 strong correlation between intensity and AHI (0.66) (41).…”
Section: Distinction By Soundmentioning
confidence: 99%
“…Snoring sound was recorded with a unidirectional electric condenser microphone placed over the trachea at the level of the cricoid cartilage using an elastic band. The sound signal was amplified and filtered using second order Butterworth pass-band filter between 70 and 2000Hz and digitized with a sampling frequency of 5000Hz and a 12-bit analog/digital converter [5].…”
Section: A Signal Acquisitionmentioning
confidence: 99%
“…Several techniques such as sound intensity calculations, power spectrum analysis, feature extraction in time and frequency domains and attempts to model snore sounds are the latest efforts giving evidence that snoring carries information on SAHS [3][4][5]. Even though these latest works added auspicious information there seems to be a lack of emphasis on how the anatomical structure of the upper airways has effect on the time production of snores.…”
Section: Introductionmentioning
confidence: 99%